Fetomaternal outcome in elevated Glucose Challenge Test and gestational diabetes - Shrestha, Abha; Kayastha, B; Pradhan, N (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To observe the maternal and fetal outcome among those having elevated Glucose Challenge Test (GCT) level and gestational diabetes mellitus (GDM). Methods: Medical record of 15,413 pregnant women booked and delivered between June 2012 and January 2018 were evaluated. GCT was performed by using 50gm glucose and diagnosis of gestational diabetes performed by using the Carpenter Coustan Criteria. Pregnancy outcomes were assessed by the antenatal events, gestation and mode of delivery. Similarly, neonatal outcomes assessed in terms of birth weights, Apgar score, congenital abnormalities, hyperbilirubinaemia, hypoglycaemia and respiratory distress syndrome. Results: The detected incidence of gestational diabetes was 2.35%. With the threshold plasma glucose level at 140 mg/ dl, 1843 women needed to undergo 100g oral glucose tolerance test and 363 women had gestational diabetes. Conclusions: It is very important to find out GDM in pregnancy as it has adverse outcomes which are preventable; it is worthwhile to detect GDM by screening in pregnancy. The 50g GCT is feasible and 100gm OGTT to find out GDM.